Serum SNTF, a Surrogate Marker of Axonal Injury, Is Prognostic for Lasting Brain Dysfunction in Mild TBI Treated in the Emergency Department - Siman, Robert; Cui, Hongmei; Wewerka, Sandi S.; Hamel, Lydia; Smith, Douglas H.; Zwank, Michael D. (Frontiers in Neurology, 2020)
Mild traumatic brain injury (mTBI) causes persisting post-concussion syndrome for many patients without abnormalities on conventional neuroimaging. Currently, there is no method for identifying at-risk cases at an early stage for directing concussion management and treatment. SNTF is a calpain-derived N-terminal proteolytic fragment of spectrin (alphaII-spectrin1-1176) generated in damaged axons following mTBI. Preliminary human studies suggest that elevated blood SNTF on the day of mTBI correlates with white matter disruption and lasting brain dysfunction. Here, we further evaluated serum SNTF as a prognostic marker for persistent brain dysfunction in uncomplicated mTBI patients treated in a Level I trauma center emergency department. Compared with healthy controls (n=40), serum SNTF increased by 92% within 24 hours of mTBI (n=95; p<0.0001), and as a diagnostic marker exhibited 100% specificity and 36% sensitivity (AUC=0.87). To determine whether the subset of mTBI cases positive for SNTF preferentially developed lasting brain dysfunction, serum levels on the day of mTBI were compared with multiple measures of brain performance at 90 days post-injury. Elevated serum SNTF correlated significantly with persistent impairments in cognition and sensory-motor integration, and predicted worse performance in each test on a case by case basis (AUC=0.68 and 0.76, respectively). SNTF also predicted poorer recovery of cognitive stress function from 30 to 90 days (AUC=0.79-0.90). These results suggest that serum SNTF, a surrogate marker for axonal injury after mTBI, may have potential for the rapid prognosis of lasting post-concussion syndrome and impaired functional recovery following CT-negative mTBI. They provide further evidence linking axonal injury to persisting brain dysfunction after uncomplicated mTBI. A SNTF blood test, either alone or combined with other markers of axonal injury, may have important utilities for research, prognosis, management and treatment of concussion.